2015
DOI: 10.1007/s00432-015-2014-2
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine in heavily pre-treated patients with relapsed or refractory multiple myeloma

Abstract: Bendamustine monotherapy is an effective treatment option for heavily pre-treated myeloma patients due to its favorable response rate and mild toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Recently, an Italian study also reported an ORR of only 29% and a median OS of 7.3 months following various bendamustine-containing salvage treatments in an unselected patient population that more accurately reflected patients encountered in clinical practice [ 18 ]. Although another retrospective study reported a better outcome with an ORR of 59% and a median OS of 17 months, the patient characteristics in that study were different to those in other studies, including ours, in terms of previous treatments and the percentage of patients refractory to their last treatment [ 19 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Recently, an Italian study also reported an ORR of only 29% and a median OS of 7.3 months following various bendamustine-containing salvage treatments in an unselected patient population that more accurately reflected patients encountered in clinical practice [ 18 ]. Although another retrospective study reported a better outcome with an ORR of 59% and a median OS of 17 months, the patient characteristics in that study were different to those in other studies, including ours, in terms of previous treatments and the percentage of patients refractory to their last treatment [ 19 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Median PFS and OS for the entire cohort were 9.3 and 12.4 months, respectively. An ORR of 59% was reported by Stöhr et al [ 16 ] in heavily treated RRMM patients with a median OS of 17 months and an EFS of 7 months. Recently, Musto et al [ 17 ] published results on 78 MM patients, most of whom were refractory to IMiDs and bortezomib.…”
Section: Discussionmentioning
confidence: 75%
“…In one of the published studies the response rate was 20% (partial response or better) with no complete responses, further 39% of patients had a minimal response, the median event-free survival (EFS) was 7 months, and the median OS was 17 months. Interestingly, patients who received a concomitant steroid had shorter OS (13 months) [ 6 ]. In another study with RRMM patients who previously received alkylators, steroids, IMiDs and bortezomib, the ORR (PR or better) was 30%, including 2% CR, the median PFS was 9.3 months, and the median OS was 12.4 months [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding safety profile, in most reports, bendamustine-based therapies were well-tolerated, and most adverse events were hematological [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Non-hematological adverse events were either associated with hematological complications, such as infections due to neutropenia, or related to other drugs, such as hyperglycemia due to steroids [ 16 ] or neuropathy due to bortezomib [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation